Effect of circulating 25-hydroxyvitamin D and antioxidant capacity level on cognitive function parameters of children with idiopathic short stature - Omyma G. Ahmed; Hala M. Sakhr; Haytham M. Ali; Lamiaa Abdlsamiee (SpringerOpen, 2020)
Abstract Background An optimal level of vitamin D is necessary for normal bone growth. Recently, vitamin D has been linked to many neurological disorders, changes in antioxidant capacity levels, and cognitive function decline in old age; thus, the aim was to evaluate the effect of vitamin D and antioxidant levels on the cognitive function parameters of children with idiopathic short stature (ISS). Results A prospective case-control study was conducted with 60 primary school-aged children with ISS who were compared to 60 unrelated healthy age- and sex-matched children as a control group. A complete clinical evaluation; anthropometric measurements; neurocognitive function parameters using the Stanford-Binet test, fifth edition; vitamin D level; total antioxidant capacity (TAC); total oxidative stress (TOS); and oxidative stress index (OSI) were measured. A total of 83.3% of children with ISS had a vitamin D level < 30 ng/ml with significantly lower vitamin D levels than the control group. The TAC level was significantly lower in children with ISS than in healthy children. Children with ISS had an average level for all of the cognitive function parameters but a lower non-verbal IQ, full-scale IQ, fluid reasoning, knowledge, quantitative reasoning, and working memory than healthy controls. A positive correlation was found between vitamin D level and all anthropometric measurements, all IQ parameters, and TAC levels in the studied children. A positive correlation was found between TAC and all IQ parameters. Conclusion Vitamin D level and antioxidant capacity level have a major impact on cognitive function parameters in children with ISS.